Marketing margin analysis of cardaba from Malita, Davao del Sur price transmission and net margins - Lamban, Ruby Jane G.; Romo, Glory Dee A. (2009)
This study was conducted to examine the marketing margins to assess the efficiency of the cardaba supply chain in Malita, Davao del Sur. In particular, this study intends to identify and examine the different marketing costs incurred by the actors in the cardaba supply chain using net margin analysis, know how price is transmitted (marketing margin analysis) , as well as the problems faced by the industry. Marketing margin analysis utilized secondary data of Philippine annual average of farm, wholesale, and retail prices, with real agricultural wage and lending rate. Fuel price is annual average Metro Manila price. The time-series data period is from 1990 to 2007. Net margin analysis used primary data that were gathered through interview method. Production and marketing costs incurred by each actor were accounted. Results showed that farm, wholesale, and retail price move together. While farm to retail level transmission is the least efficient price transmission. Labor cost accounted for the highest cost at the farm level. The study found the actors who supplied cardaba in Manila gained more compared to supplying processors. The study also found that it would increase the competence of the Malita cardaba industry for actors to unify and form an organization that will take charge of consolidating and create a market linkage for their product. In this type of organization, productivity issues as well as pre-harvest and post harvest issues can also be addressed.
Thesis, Undergraduate (BS Agribusiness Economics)--University of the Philippines, Mindanao